Ações de cuidado à família do usuário de substâncias psicoativas: perspectiva de profissionais e familiares - Siqueira, Daiana Foggiato de (2018)
The use of psychoactive substances is a concern both for the health of the user and for the family, impairing the coexistence between family members, income at work, social, relational, and economic aspects of the people involved. This study aims to analyze the care actions aimed at the attention to the family of the user of psychoactive substances in relation to the reciprocities of the perspectives of relatives and professionals of a Center of Psychosocial Attention. This is a phenomenological research in the light of the Social Phenomenology of Alfred Schütz, which was carried out with 13 professionals and 12 relatives of users of psychoactive substances who perform treatment at the Center for Psychosocial Care Alcohol and drugs of a municipality in the interior of the state of Rio Grande do Sul, Brazil. The data were collected through the phenomenological interview with guiding questions for the team of professionals and for the families of the users of these services. In the comprehensive analysis of the meaning of care actions aimed at the care of the user of psychoactive substance users, care actions were made to the family members from the professionals' perspective, as well as their intentions regarding these care actions. It was revealed that there is a convergence between the intentions and expectations of the participants, since both the intentions of the professionals and the expectations of the family members were based on the effectiveness in the treatment of the user. It was also revealed that there is convergence between the actions of professionals and family members regarding the family group, reception and orientation. The accomplishment of this research allowed to widen the look to the world of the life of the relatives who seek care in the Center of Psychosocial Attention. In addition, he sought to give voice, in addition to the professionals, to the relatives of users of psychoactive substances, from the opportunity to expose about their lived experiences in relation to care actions focused on attention to the family member.